International journal of human capital and information technology professionals (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
"The International Journal of Human Capital and Information Technology Professionals (IJHCITP) focuses on the IT field from the outlook of industry professionals and covers multidisciplinary themes such as human resource management, sociology, psychology, and management. Representing IT professionalism from the human capital point of view, IJHCITP publishes original research papers, research notes, reviews, and cases on all aspects of IT professionalism, technology-related careers, personnel empowerment, and organizational management. This journal emphasizes articles linking theory with application or critically analyzing cases with the objective of identifying good practice in the management of IT human capital."--Provided by publisher.